HOMOTOPY PERTURBATION METHOD FOR SOLVING THE NONLINEAR WAVE EQUATIONS - Ahmood, Ranen Z (Al-Nahrain Journal of Science, 2010)
In this paper, we present the approximated solutions of special types of the nonlinear partialdifferential equations in one dimension namely the nonlinear wave equations by using thehomotopy perturbation method. Some examples are solved to show the efficiency of this methodand a comparison is made with the Adomian decomposition method.Keywords:homotopy perturbation method,nonlinear wave equations,Adomian decomposition method,exact solutions